Cognitive Deficits Related to Focal Spike Location in Benign Partial Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The topographic relation between focal spikes and neuropsychological deficits in children with benign partial epilepsy (BPE) was investigated using magnetoencephalography (MEG), electroencephalography (EEG) and MRI in a study of 27 children at University Children's Hospital, Tuebingen, Germany, and University of Trento, Italy.